2008
DOI: 10.2323/jgam.54.205
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community in the rhizosphere of young maize seedlings is susceptible to the impact of introduced pseudomonads as indicated by FAME analysis

Abstract: Two species of Pseudomonas (i.e. P. chlororaphis or P. putida) derived from a maize rhizosphere were studied for their impact on the structure of the microbial community in the rhizosphere of young maize seedlings after inoculation. The culturable bacteria and total microbial communities were analyzed based on profiles of whole-cell fatty acid methyl esters (MIDI-FAME). The introduction of Pseudomonas species resulted in the shift from the Gram-positive dominated culturable community in the rhizosphere of unin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This discrepancy between results of direct extraction of fatty acids from soil and microbial colonies cultured on agar media has been reported in several studies (Bååth et al, 2005;Ibekwe & Kennedy, 1998;Kozdrój, 2008). Mostly Gram-negative bacteria may have predominated over the total community of soil bacteria in the heap sites, as indicated by high concentrations of monounsaturated fatty acids and presence of hydroxy and cyclopropane FAMEs.…”
Section: Fame Patterns Of Microbial Communitymentioning
confidence: 69%
“…This discrepancy between results of direct extraction of fatty acids from soil and microbial colonies cultured on agar media has been reported in several studies (Bååth et al, 2005;Ibekwe & Kennedy, 1998;Kozdrój, 2008). Mostly Gram-negative bacteria may have predominated over the total community of soil bacteria in the heap sites, as indicated by high concentrations of monounsaturated fatty acids and presence of hydroxy and cyclopropane FAMEs.…”
Section: Fame Patterns Of Microbial Communitymentioning
confidence: 69%
“…These bacteria are often identified as dominant taxa of cultivable microbial populations from rhizosphere of various crop plants (Aravind et al 2009;Caesar-TonThat et al 2007;Çakmakçi et al 2006;Germida and Siciliano 2001;Kozdrój 2008;Park et al 2005;Rusznyák et al 2008;Vessey 2003). Among the Gram-positive bacteria identified by FAME, species of Bacillus, Brevibacillus, Paenibacillus and Arthobacter occurred in both barley and alfalfa soil (Caesar-TonThat et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The field of rhizosphere microbiology of tea garden soil ecosystems is unexplored and in this work, we have isolated the bacterial population from the rhizosphere of tea plants production zones of various agro climatic regions in Rize and Trabzon during June-September, 2007-2008. The study area is located on the eastern Black Sea region, most in Rize, between 40°50′ and41°20′ N and38°49′ and41°28′ E. The tea gardens were established between 1938-1944 years and now all of them are between 65-70 years old.…”
Section: Soil Samples Isolation and Identification Of Bacteriamentioning
confidence: 99%
“…However, there have also been studies that have shown a direct effect on the plant microbiome due to bacterial inoculations. Examples include inoculations of Rhizobium species in faba beans ( Vicia faba L.) ( Zhang et al, 2010 ) and soybean ( Glycine max L.) ( Zhang et al, 2011 ), Proteus vulgaris in Kimchi cabbage ( Brassica rapa L.) ( Bhattacharyya and Lee, 2016 ), and Pseudomonas species in maize ( Kozdrój et al, 2004 ; Kozdrój, 2008 ). The advent of metagenomic sequencing to examine the effects of microbial inoculation on the non-target soil microbiome will be a research area that will see great developments in the near future ( Martínez-Hidalgo et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%